Atmospheric-pressure plasma-irradiation inhibits mouse embryonic stem cell differentiation to mesoderm and endoderm but promotes ectoderm differentiation. (21st March 2016) - Miura, Taichi; Hamaguchi, Satoshi; Nishihara, Shoko
Abstract: Recently, various effects of low-temperature atmospheric-pressure plasma irradiation on living cells have been demonstrated, such as tissue sterilization, blood coagulation, angiogenesis, wound healing, and tumor elimination. However, the effect of plasma-irradiation on the differentiation of mouse embryonic stem cells (mESCs) has not yet been clarified. A large number of reactive species are generated by plasma-irradiation in medium, of which hydrogen peroxide (H2 O2 ) is one of the main species generated. Here, we investigated the effect of plasma-irradiation on the differentiation of mESCs using an embryoid body (EB) formation assay with plasma-irradiated medium or H2 O2 -supplemented non-irradiated medium. Our findings demonstrated that plasma-irradiated medium potently inhibits the differentiation from mESCs to mesoderm and endoderm by inhibiting Wnt signaling as determined by quantitative polymerase chain reaction and immunoblotting analyses. In contrast, both the plasma-irradiated medium and H2 O2 -supplemented non-irradiated medium enhanced the differentiation to epiblastoid, ectodermal, and neuronal lineages by activation of fibroblast growth factor 4 (FGF4) signaling, suggesting that these effects are caused by the H2 O2 generated by plasma-irradiation in medium. However, in each case, the differentiation to glial cells remained unaffected. This study is the first demonstration that plasma-irradiation affects the differentiation of mESCs by the regulation of Wnt and FGF4 signaling pathways.